Blight, Ed., Narrative Of The Life Of Frederick Douglass, An American Slave - Dalton, C. David (Teaching History: A Journal of Methods, 1993)
The 1845 narrative of Frederick Douglass’s life was, arguably, the most widely read and influential slave narrative prior to the Civil War. Certainly, it is was the best written. His story is one that should be familiar to students of the "Middle period," and this short text can be used as a fine supplement in an introductory college survey class or courses dealing with slavery or the Civil War. For those teachers looking to extract a few interesting and first-hand details of what a slave’s life was like, I can think of no better source than this.